Highly scalable prefusion-stabilized RSV F vaccine with enhanced immunogenicity and robust protection - Qingrui Huang; Qingyun Lang; Yao Li; Fengjie Wang; Xiaonan Han; Ling Luo; Xiaomin Duan; Xuerong Cao; Yue Wang; Yu Bai; Yaxin Song; Yanpeng Xu; et al. (Nature Communications)
Abstract Stabilizing the RSV F protein in its prefusion conformation is crucial for effective vaccine development but has remained a significant challenge. Traditional stabilization methods, such as disulfide bonds and cavity-filling mutations, have been labor-intensive and have often resulted in suboptimal expression levels. Here, we report the design of an RSV prefusion F (preF) antigen using a proline-scanning strategy, incorporating seven proline substitutions to achieve stabilization. The resulting variant, preF7P, is structurally and biochemically validated to maintain the correct prefusion state. PreF7P demonstrates superior immunogenicity with a 1.8-fold increase in neutralizing antibody titers when compared to DS-cav2, and provides protection from clinical disease against both RSV A and B strains in female murine and female cotton rat models. In clinical development, preF7P exhibits high expression levels (~10 g/L) in clinical-grade CHO cells. The clinical-grade vaccine elicits robust immunogenic responses across female mice, female SD rats, and both male and female cynomolgus macaques, significantly boosting RSV pre-infection neutralizing antibody titers, and providing sustained protection for at least six months in female mice. This proline-scanning strategy offers a streamlined approach for stabilizing class I fusion proteins, potentially accelerating the development of vaccines for other pathogens.